Private Sector Financing and the role of Risk-bearing Instruments. Country report: Azerbaijan - European Investment Bank (European Investment Bank (EIB), 2013)
This study was commissioned by the EIB with funding from the Eastern Partnership Technical Assistance Trust Fund, EPTATF. The study assesses the financing needs of the SMEs in the Eastern Partnership countries and the market failures that are constraining the development of the SME sector. In addition the study addresses the funding needs of the intermediaries that specialize in SME financing and examines the potential for different types of financial products including equity, guarantees, trade finance and other risk-bearing instrument.
Keywords: 330